2021
DOI: 10.1111/faf.12597
|View full text |Cite
|
Sign up to set email alerts
|

Nudging fisheries and aquaculture research towards food systems

Abstract: Food system is a powerful concept for understanding and responding to nutrition and sustainability challenges. Food systems integrate social, economic, environmental and health aspects of food production through to consumption. Aquatic foods are an essential part of food systems providing an accessible source of nutrition for millions of people. Yet, it is unclear to what degree research across diverse disciplines concerning aquatic foods has engaged food systems, and the value this concept has added. We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 115 publications
(342 reference statements)
1
27
0
Order By: Relevance
“…This emphasis resonates well with the current shift in discourse from a dominant focus on fish as either an economic resource from which to profit or as stocks in need of conservation, to valuing fish primarily as a micronutrient-dense resource to be sustainably used as food (e.g., Cohen et al 2019;Bennett et al 2021;Golden et al 2021). In this increasingly influential discourse of seeing fisheries as food systems (Simmance et al 2021), the significance of the skills and labor of small-scale traders for low-income consumers' access to safe and high-quality aquatic foods, should take center stage. In our marketplace and market woman-centered FSN perspective, we analyze (1) how fish sold in the market arrived there (i.e., traders' role in fish availability, access, and stability) and (2) market women's practices for enhancing fish safety and quality (i.e., traders' role in fish utilization) (HLPE 2020: 10).…”
Section: Introductionmentioning
confidence: 61%
“…This emphasis resonates well with the current shift in discourse from a dominant focus on fish as either an economic resource from which to profit or as stocks in need of conservation, to valuing fish primarily as a micronutrient-dense resource to be sustainably used as food (e.g., Cohen et al 2019;Bennett et al 2021;Golden et al 2021). In this increasingly influential discourse of seeing fisheries as food systems (Simmance et al 2021), the significance of the skills and labor of small-scale traders for low-income consumers' access to safe and high-quality aquatic foods, should take center stage. In our marketplace and market woman-centered FSN perspective, we analyze (1) how fish sold in the market arrived there (i.e., traders' role in fish availability, access, and stability) and (2) market women's practices for enhancing fish safety and quality (i.e., traders' role in fish utilization) (HLPE 2020: 10).…”
Section: Introductionmentioning
confidence: 61%
“…The dried fish literature is a resource on which to draw as the fisheries literature shifts towards viewing fisheries as food systems (e.g. Arthur et al, 2022; Campling & Havice, 2018; Foley & Mather, 2018; Simmance et al, 2022), and in relation to the Small‐scale Fisheries Guidelines (FAO, 2015) and the Sustainable Development Goals (HLPE, 2020). At the same time, the general fisheries literature provides tools and insights with which to address important blind spots in the literature on dried fish, particularly around governance (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although roughly half of total eligible studies incorporated the sampling of both women and men, further inspection revealed just a fraction of these presented some form of disaggregated results, incorporated a gender‐specific component into study designs or analysis, or attempted to interpret the interaction between gender and livelihood diversification outcomes. The scarcity of reporting on gendered roles in fish‐based livelihoods and the broader aquatic food systems literature has been noted before (Simmance et al, 2021; Stacey et al, 2019), and demonstrates limited engagement with societal contexts that influence the outcomes from diversification processes.…”
Section: Discussionmentioning
confidence: 99%